Range extension and emended description of the threatened Psychotria catanduaniensis (Rubiaceae) in the coastal area in Palanan, Isabela, Luzon, Philippines. Issue 4 (24th January 2022) - Biag, Rachel D.; Alejandro, Grecebio Jonathan D.
Abstract : A new distribution record of Psychotria catanduaniensis Sohmer & A.P. Davis is reported. It was last observed 91 years ago, but as reported here a single individual of this threatened species was recently found in a coastal area in Palanan, Isabela, Luzon, Philippines. The species is characterized by large polymorphic leaves and a terminal, paniculate, sessile and trichotomous inflorescence. An emended description of the species, particularly focussing on its bracts, bracteoles and flowers which are lacking in the type material and not previously studied, morphological comparison with allied species and its current conservation status are also provided.